Reception of Qur’anic Ecotheological Values in Bima Muslim Local Wisdom: A Living Qur’an Study through Jauss’ Reception Theory - Muhammad Aminullah; Syamsurijal (QOF, 2025)
This study examines the reception and praxis of Qur’anic eco-theological values within the cultural life of the Muslim community of Bima, West Nusa Tenggara, Indonesia, through a living Qur’an approach combined with Hans Robert Jauss’s reception theory. It investigates how Qur’anic concepts such as tawḥīd, khilāfah, amānah, and ecological balance are received, interpreted, and internalized through local wisdom, including the philosophy of Maja Labo Dahu, the ethical principle Ngaha Aina Ngoho, and cultural practices such as Rimpu and Peta Kapanca. Using qualitative methods comprising literature review, cultural observation, and contextual tafsīr analysis, the study finds that these traditions function as concrete modes of cultural reception that translate Qur’anic eco-theological values into everyday ethical practices, particularly in fostering environmental responsibility and social restraint. However, the analysis also reveals interpretive limits and contextual constraints, where specific ecological meanings are selectively emphasized while others remain implicit or symbolic. Theoretically, this study contributes to living Qur’an scholarship by demonstrating how reception theory can be employed to map the horizon of expectation through which Qur’anic meanings are culturally negotiated. Empirically, it highlights local wisdom as both a medium and a boundary for the internalization of Islamic ecological ethics in addressing contemporary environmental challenges.